Optimization of Communication Path Planning Method for Low Earth Orbit Constellation Based on Dijkstra Algorithm - YIN Shuming; XUE Chengcheng; HAO Liyun; ZHANG Xinjun (天地一体化信息网络)
Complex network topologies and unbalanced uses of network resources are key problems in communication path planning for low earth orbit constellations. To address these issues, an optimization path planning method considering time delays, loads and task priorities was proposed. In this method, weighted graphs were used to characterize interconnections between satellites, and Dijkstra algorithm was improved to implement parallel computing and adapt to dynamically changing networks of low earth orbit constellations. Results of simulations based on STK and Python demonstrated that the method presented by this paper performs well in terms of dynamic stability and plans optimization paths accurately, and the planning time decreased by about 70% on average compared with the original algorithm.